Effect of Cashless Policy on Financial Sector Development in Nigeria - Enueshike, Peter; Oluchukwu, Dorathy Anyanwu; Ajidani, Moses Sabo (International Journal of Finance, 2025)
Purpose: The purpose of this study is to examine the effect of cashless policy on financial sector development in Nigeria specifically it sought to examine the effect of mobile banking automated teller machine and point on sale on financial sector development in Nigeria. Methodology: The study adopted VAR methodology coupled with the the Philips-Perron test (PPT) to test the stationarity of the variables and ordinary least square (OLS) estimation technique to confirm the robustness of the model, error correction model (ECM) to determine the speed of adjustment, using annual time series data (secondary data) covering the period 2012-2022. Findings: The findings revealed that there is positive relationship between ATM and financial sector development is as a result of e-transaction through technology acceptance and diffusion of innovation of cashless policy in Nigeria. The result also revealed that point of sale (POS) and mobile banking (MB) had an inverse and significant effect on financial sector development in Nigeria. This insignificant effect can be attributed to poor internet and power supply, inadequate supply of point-of-sale devices and unfriendly deposits money banks mobile applications of some banks in Nigeria. Mobile banking services, despite having an inverse relationship with financial sector development, reduce commercial bank queues due to their ease of use. Unique Contribution to Theory, Practice and Policy: The study recommends that to promote cashless economy, massive sensitization campaigns and reliable power supply are necessary. Furthermore, the regulatory bodies must address issues such as faulty ATM machines, robbery, limited access and excessive charges.